Efektivitas Pembelajaran PAI Dengan Menggunakan Model Pembelajaran Pelatihan Kesadaran Diri Siswa - Raito, Raito; Nauval, Ihfad Ahmad (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
This research is motivated by the ineffective learning outcomes due to students' low self-awareness in participating in learning activities. This is evident from the lack of achievement of learning objectives and the presence of students who do not meet the Minimum Completion Criteria (KKM) in Islamic Education (PAI). Self-awareness is crucial in learning activities, yet it remains a significant challenge for students. The objective of this study is to describe the effectiveness of Islamic Education (PAI) learning using a self-awareness training model. It is anticipated that the use of this model will have a positive impact on enhancing students' self-awareness. The research method employed is descriptive-analytical, chosen to gather factual data with interpretation. Primary and secondary data were collected through direct fieldwork using questionnaires, interviews, and observations. Data validation utilized triangulation. The findings indicate that the self-awareness training model in Islamic Education (PAI) positively impacts the effectiveness of learning. This improvement is attributed to teachers selecting substantive teaching materials, employing appropriate methods, and using functional learning media.  Keywords: Effectiveness of Islamic Education Learning, Self-Awareness Training Model